Bradea borrerioides (Rubiaceae), a new species from Brazilian inselbergs - Oliveira, Juliana Amaral De; Sobrado, Sandra Virginia (Phytotaxa, 2016)
Bradea borrerioides is here newly described as a species endemic to the inselbergs of Espírito Santo and Minas Gerais states, Brazil. It differs from all other Bradea species by its frondose-bracteate synflorescence with paraclades disposed in a monocasial branch-pattern. Affinities, diagnostic characters, distribution and conservation status are discussed.